Unity, a priceless gift and needs to be well-looked-after - UMP, PNC (2019)
Unity is an invaluable gift and needs to be uphold as well as appreciated by all people living in a multi racial country like this country that we love. Unity is a creation that comes from people with diverse ethnicity and religions having mutual respect of one another and are always thoughtful and mindful of their sensitivity, religion and culture, for the sake of harmony.